PERAN GURU PENDIDIKAN AGAMA KRISTEN DALAM DEKADENSI MORAL SISWA MENGHADAPI ERA DIGITAL - Butarbutar, Imelda (Jurnal Suluh Pendidikan, 2022)
Today moral issues in the midst digital flows are become an important think. This problem will make a bad impact on student morale. Therefore, Christian education teachers have a role in efforts to overcome students' moral decadence to overcame the danger posed to the student morale. The research conducted is a qualitative method with a literature study that aims to describe the role of Christian education teachers to overcome student’s moral dekadency in the digital era. For this reason, first, teachers must know about the base of moral decadence and digital challenges, so that they can provide solutions to their students. The second things, the teacher conveys moral values ​​from the point of view of the Bible as the foundation of norms of life that has taught and applied it in their daily life. The third thing is that Christian religious teachers must become a role models, especially in the cyberspace or digital, so that the students can see and imitate the attitudes of teachers in real and virtual communities.